(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The Question of identity is always a difficult one, andespecially for those who are culturally displaced. The immigrants are those whogrow up in two worlds. Jhumpa Lahiri believes that for immigrants, thechallenge of exile, the loneliness, the constant sense of alienations, theknowledge of and longing for a lost world are more explicit and distressingthan for their children. The Namesake is essentially, a story about thestruggles and hardships of a Bengali couple who immigrate to the United Statesto form a life outside of everything they know.